Tanoh Kamoe: Tarek Pukat In The Form Of A Two-Part Musical Composition - Aqilah, Fatin; Surayya, Yade; Sina, Ibnu; Syaputra, Weldi (Institut Seni Indonesia Padangpanjang, 2025)
This composition raises the tradition of Tarek Pukat, an art and culture from the coastal communities of Aceh, as the basis for creating a musical composition entitled Tanoh Kamoe. This tradition, which reflects the spirit of cooperation and the life of fishermen, is adapted into a two-part musical composition using the Acehnese Fusion Ensemble format. The original melody of Tarek Pukat, which is simple and repetitive, is developed through musical processing techniques such as augmentation, diminution, imitation, and sequence. This composition consists of two parts: Part I emphasizes traditional musical instruments such as serune kale, rapa’i, vocals, and flutes, while Part II presents a modern nuance with orchestral instruments and a combo band. With a total duration of 15 minutes, this work describes the journey of fishermen from preparation, fishing, to sharing the catch. The creation method involves exploring music theory, interviews, and using software such as Sibelius. Through this work, it is hoped that local traditions can be preserved and recognized by the wider community while providing innovation in the processing of tradition-based musical art. Ensemble